"أحاديث قطع المرأة للصلاة بمرورها" دراسة حديثية فقهية وفق خطوات التعامل مع مختلف الحديث - Al-Obaid,S.A.J. (Universiti Sains Islam Malaysia, 2024)
This study aims to jurisprudentially present the issue of " the Interruption of One's Prayer if a Woman Walks in Front" in Hadiths, and dealing with it according to the ways of dealing with Mukhtalif al Hadith (Hadith that cause disputes). After the study, it was concluded that there is no significant abrogation in the issue, so we resort to combining and reconciling the evidence. Through the study, it was found that scholars had various opinions concerning combining these Hadiths that are grouped in 3 jurisprudential opinions; the first says: nothing interrupts a prayer; the second says: only a black dog interrupts a prayer; and the third says: a woman, a black dog, or a donkey interrupt a prayer. After reviewing and discussing the evidence, the researcher ruled in for the interruption of one's prayer if a woman walks in front, and the differentiation between walking and lying down. Allah knows best.